THE RELATIONSHIP BETWEEN CELEBRITY WORSHIP TO STREET TEENAGERS' SELF-IDENTITY IN MALANG CITY - Nina Rizka Rohmawati (Nurse and Health: Jurnal Keperawatan, 2023)
Background: Adolescence is a phase that must be passed through physical, mental, emotional and social changes. In this phase, adolescents begin to have a developmental task, namely self-identity. Adolescents with good self-identity will achieve developmental tasks well, while adolescents with low self-identity may experience identity confusion which results in deviant behaviors. Self-identity is influenced by several factors, one of which is the celebrity worship factor. Objectives: To describe the relationship between celebrity worship to street youth self-identity. Methods: Descriptive with a cross sectional approach. The 130 respondents participated on this study by using purposive sampling technique. The measurement tools used were the Celebrity Attitude Scale for the variable (celebrity worship) and the Identity Style Inventory for the Self-Identity variable. Results: Bivariate analysis with Spearman rho celebrity worship (p value = 0.027, r = 0.194). Conclusion: There is a relationship between celebrity worship and self-identity among street children in Malang City, East Java